Detection of the Breast Cancer from Thermal Infrared Images - Dwi Nurhayati, Oky; Sri Widodo, Thomas; Susanto, Adhi (Jurnal Sistem Komputer, 2011)
Thermography can be used as part of an earlydetection tool which gives women of all ages the opportunityto increase their chances of detecting breast diseases at avery early stage. Breast thermography is a noninvasiveprognostic procedure which can predict a tumor growth ratein breast cancer patients. The objective of this research is toacquire the potential of the statistical characteristics of thebreast thermogram images for the detection of the breastcancer.For this research we use thermal data images fromSardjito hospital at Yogyakarta, from normal and abnormalbreast (detected breast cancer). Firstly, download the breastimage thermograms from the InsideIR software of FlukeTi20 and save them as the inputs to our image processingprogram. Then adjust the format of the images, convert tograyscale images, and crop them to separate the suspectedobjects from the background. Finally we tabulated thestatistical characteristics of the objects which are the means,standard deviations, and entropy to reveal the abnormalitiesof breast thermograms.The results show that the method are promising todetect the abnormality on the breast thermogram images.The normal breast thermograms have minimum entropieswhich differ from those abnormal thermograms in the earlystage of breast cancer and thesignificantly from the moreadvanced of breast cancer.